2017
DOI: 10.1007/s10545-017-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive profiles in MSUD school‐age patients

Abstract: Maple syrup urine disease (MSUD), an inborn error of amino acids catabolism is characterized by accumulation of branched chain amino acids (BCAAs) leucine, isoleucine, valine and their corresponding alpha-ketoacids. Impact on the cognitive development has been reported historically, with developmental delays of varying degree. Currently, earlier diagnosis and improved management allow a better neurodevelopment, without requirement of special education. However, specific impairments can be observed, and so far,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…19 In our study, we tested the overall IQ ability (FSIQ). A French study by Bouchereau et al 42 found that some of their group of MSUD patients had verbal abilities that were significantly better developed than their nonverbal/performance skills. Future studies in our own centre would favour early testing of our MSUD cohort to detect any similar issues.…”
Section: Discussionmentioning
confidence: 99%
“…19 In our study, we tested the overall IQ ability (FSIQ). A French study by Bouchereau et al 42 found that some of their group of MSUD patients had verbal abilities that were significantly better developed than their nonverbal/performance skills. Future studies in our own centre would favour early testing of our MSUD cohort to detect any similar issues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liver transplantation is an effective treatment, which may reduce the progression of brain damage; however, liver transplantation is not sufficient to reverse pre-existing neurological damages (32). Therefore, early treatment of MSUD is essential to allow normal neuronal development (33).…”
Section: Discussionmentioning
confidence: 99%
“…Such treatment is difficult to maintain in the long term and is largely incompatible with a normal quality of life. Further, it does not prevent long-term neurocognitive 5 and psychiatric impairments 6 , the latter affecting roughly 30% of the patients after the age of 20 years 6 . Orthotopic liver transplantation (OLT), was shown as an effective MSUD therapy allowing removal of dietary restrictions, full protection from acute decompensations during illness 7 , 8 , arrest of neurocognitive impairment progression 3 , 9 , prevention of life-threatening cerebral edema 3 , metabolic and clinical stability 9 .…”
Section: Introductionmentioning
confidence: 99%